Pengembangan Media Pembelajaran Motion Graphic Untuk Siswa Kelas XI Pada Desain Multimedia Di SMK N 1 Cibadak - Damayanti, Damayanti; Wulandari, Heni (utile: Jurnal Kependidikan, 2018)
This research aims to develop the motion graphic learning media as a positive stimulusfor students to foster creativity, interesting and innovative media. This study also aims to determinethe feasibility of learning media motion graphic. This research is a development research usingBorg and Gall development model that is (1) Potency and problem, (2) Data collection, (3)Product design, (4) Design validation, (5) Design revision, (6) Product trial, (7) Revisions, (8)Trial usage / field trials, (9) Product revisions, and (10) Mass production. The results of thefeasibility research of Media Learning of motion graphic based on the assessment: 1) ExpertMaterial obtained average score of 4.3 which belongs to Very Eligible category, 2) Design Expertobtained average score of 4 which belongs to Eligible category, 3) Media Expert obtained flat 3,8score included in Very Eligible category, 4) Small group trial obtained average score 4,2 whichbelongs to Eligible category, 5) Large group trial obtained by average score 4 which belongs toEligible category.